Visioning multicultural education : past, present, future - Baptiste, H. Prentice; Haynes Writer, Jeanette; Gale (Firm) (New York, New York : Routledge, 2021)
Organized by the National Association of Multicultural Education (NAME), this book explores the organic relationship between the past, present, and future of multicultural education. In particular, it addresses the various forms of recent social upheaval, from educational inequities and growing economic divides to extreme ideological differences and immigration conflicts.
Foreword / Gary R. Howard -- Introduction / H. Prentice Baptiste and Jeanette Haynes Writer -- The reaffirmation of multicultural education / Geneva Gay -- The continuing multicultural education of a Black teacher educator : reflections on a journey toward my referent other-self / Patricia L. Marshall -- Challenging racism and colonialism through ethnic studies / Christine E. Sleeter -- Imagining : "A letter on racial progress" : James Baldwin's keynote at the 30th Annual NAME Conference : evolution of multicultural education, 21st century / Carl A. Grant -- Truth, land, and sovereignty : Native American intellectual activists, their critique of settler colonialism, and the unsettling of multicultural education / Jeanette Haynes Writer & Kristen B. French -- Testing for whiteness? : how high-stakes, standardized tests promote racism, undercut diversity, and undermine multicultural education / Wayne Au -- Inclusive diversity and robust speech : examining a contested intersection / Carlos E. Cortés -- Education in times of mass migration / Angela M. Banks -- Transforming citizenship education in global societies / James A. Banks -- Afterword / Bette Tate-Beaver.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Multicultural education -- United States; Minorities -- Education -- United States; Educational equalization -- United States; Education and globalization -- United States